PENGATURAN JUMLAH CABANG UTAMA DAN PENJARANGAN BUAH TERHADAP MUTU BENIH TOMAT VARIETAS KALIURANG (Lycopersicum esculentum MILL) - Sri Sugihartiningsih; Agus Wartapa (Universitas Sebelas Maret, 2008)
This research used factorial device 3x3 that compiled pursuant to Randomized Completely Block Design consist of 2 factors and 3 restating. First factor was arrangement of amount main branch, consist of 3 level, that were: 1 main branch, 2 main branch, and 3 main branch. Second factor was fruit seldom, consist of without seldom, seldom 15% and seldom 30%. Data was analysed by manner sidik, if there were significant continued with Duncan Multiple Range Test level 5%.Result of research indicated that arrangement amount of main branch 3 branch and fruit seldom equal to 15% or 30% have significant an effect to high crop, energy grow seed, heavy seed 1000 item.